Evaluasi Layanan Teknologi Informasi Menggunakan Kerangka Kerja Information Technology Infrastructure Library - Pratama, Arya; Wella, Wella (Maranatha University Press, 2024)
This study aims to evaluate PT Gramedia Asri Media to find out whether the company's IT services meet the best standards of the ITIL V3 Service Operations framework. Service Operations focus includes Problem Management, Incident Management, Access Management, Request Fulfillment, and Event Management. Evaluation is carried out in four stages: planning, field inspection, reporting, and follow-up. The results indicate the maturity level of IT service implementation. For data collection, questionnaires were distributed to five people who were surveyed and interviewed with the heads of engineering services and support staff. The results show that the company's IT service maturity level is at level one. In addition, this research produced seventy suggestions for companies to improve their IT services. The results show that almost all suggestions were well received by the company, and some of them have been implemented at PT Gramedia Asri Media. However, of course, with the problems discovered from this research, there will be a desire to improve service and performance.